Respuesta :

[tex]\implies {\blue {\boxed {\boxed {\purple {\sf {C.\:None\:of\:the\:above.}}}}}}[/tex] ✔

[tex]\:\large{\boxed{\frak{ Step-by-step\:explanation: }}}[/tex]

A. [tex]x - ( - x) = -x[/tex]

Let us first solve for L. H. S.

We have,

[tex]x - ( - x)[/tex]

[tex] = x + x[/tex]

[tex] = 2x[/tex]

[tex]≠ - x[/tex]

[tex]≠ R. H. S. [/tex]

Hence, option A is incorrect.

B. [tex]0 - ( - x) = - x[/tex]

Solving for L.H.S. , we have

[tex] = 0 - ( - x)[/tex]

[tex] = + x[/tex]

[tex]≠ - x[/tex]

[tex]≠ R. H. S. [/tex]

Hence, option B is ruled out too.

Therefore, the correct answer is [tex]\sf\red{ option\:C}[/tex].